Odpowiedzi

Najlepsza Odpowiedź!
2010-02-27T17:49:26+01:00
6x-3y=9
x+5y=-9.5

6x-3y=9
x = -9,5 -5y

6*(-9,5 -5y) -3y=9
-57-30y-3y=9 /+57
-33y = 66 /:-33
y = -2

podstawiamy wynika do x+5y=-9.5
x+5*(-2) = -9,5
x-10 = -9,5
x = 0,5

spr
6x-3y=9
6 * 0,5 -3 * (-2) = 3+6 = 9
1 2 1
2010-02-27T17:52:22+01:00
6x-3y=9
x+5y=-9.5 /x(-6)

6x-3y=9
-6x-30y=57
dodajemy

-33y=66
y=-2

x-10y=-9.5
x=0.5

odp
x=0.5
y=-2
1 5 1
2010-02-27T17:54:33+01:00
6x-3y=9
x+5y=-9.5/-5y

6x-3y=9
x=-9.5-5y

6(-9.5-5y)-3y=9
x=-9.5-5y

-54-30y-3y=9
x=-9.5-5y

-54-33y=9/+54
x=-9.5-5y

-33y=63/:(-33)
x=-9.5-5y

y=-1.9
x=-9.5-5(-1.9)

y=-1.9
x=-9.5+10.45

y=-1.9
x=0.95